2020
DOI: 10.1002/ange.202011273
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific Platinum(IV) Complex Deters Breast Cancer via Interposing Inflammation and Immunosuppression as an Inhibitor of COX‐2 and PD‐L1

Abstract: Breast cancer (BC) is one of the most common malignancies in women and often accompanied by inflammatory processes.Cyclooxygenase-2 (COX-2) playsavital role in the progression of BC,c orrelating with the expression of programmed death-ligand 1(PD-L1). Overexpression of PD-L1 contributes to the immune escape of cancer cells,a nd its blockade would stimulate anticancer immunity.T wo multispecific platinum(IV) complexes DNP and NP were prepared using non-steroidal antiinflammatory drug naproxen (NPX) as axial lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
0
21
1
Order By: Relevance
“…For prodrug 21 , IC 50 values varied from 0.34 to 0.17 µM, which is up to 187-fold more than that of cisplatin, while prodrug 10 showed IC 50 values from 1.11 to 0.4 µM. It is worth noting that the IC 50 values obtained by Jin et al for prodrug 10 differ significantly from the data reported by Tolan et al; in particular, for the MCF-7 breast cancer cell line, IC 50 values for prodrug 10 in the study by Jin et al are 26-fold higher, and for the MDA-MB-231 triple negative breast adenocarcinoma cell line, IC 50 values are 21-fold higher than in the paper by Tolan et al ( Table 8 ) [ 28 ].…”
Section: Dual-action Pt(iv) Prodrugs With Nsaid Axial Ligandscontrasting
confidence: 58%
See 3 more Smart Citations
“…For prodrug 21 , IC 50 values varied from 0.34 to 0.17 µM, which is up to 187-fold more than that of cisplatin, while prodrug 10 showed IC 50 values from 1.11 to 0.4 µM. It is worth noting that the IC 50 values obtained by Jin et al for prodrug 10 differ significantly from the data reported by Tolan et al; in particular, for the MCF-7 breast cancer cell line, IC 50 values for prodrug 10 in the study by Jin et al are 26-fold higher, and for the MDA-MB-231 triple negative breast adenocarcinoma cell line, IC 50 values are 21-fold higher than in the paper by Tolan et al ( Table 8 ) [ 28 ].…”
Section: Dual-action Pt(iv) Prodrugs With Nsaid Axial Ligandscontrasting
confidence: 58%
“…Recently, Jin et al described two cisplatin-based naproxen-containing platinum(IV) prodrugs [ 28 ]. Two highly potent cisplatin prodrugs with one (NP, 10 ) or two (DNP, 21 ) naproxen moieties in the axial position were obtained ( Figure 10 ).…”
Section: Dual-action Pt(iv) Prodrugs With Nsaid Axial Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 More recently, Guo and Wang’s group reported the efficient antitumor performance of dual naproxen platinum(IV) complex 2 . 40 It targeted COX-2 and PD-L1 via multiple pathways to significantly inhibit the immune escape of tumor cells and finally improve antitumor efficacy. Thereby, naproxen platinum(IV) complex represents a promising scaffold for further development of novel platinum drugs.…”
Section: Introductionmentioning
confidence: 99%